A study on public transportation towards UiTM Jengka student satisfaction / Mohd Akmal Mohd Aduros, Muhammad Rabani Mohd Arif and Muhammad Zul Helmi Suparlan - Mohd Aduros, Mohd Akmal; Mohd Arif, Muhammad Rabani; Suparlan, Muhammad Zul Helmi (2012)
The efficiently and effectively transportation system is an important for the development of a country. Without a good system and good infrastructure, a country cannot develop economically and socially. In addition, the convenience and needs of society also influenced the development of a country's especially in public transportation systems. A country also is measured by the level of improvement from the element such as good transportation and good infrastructure systems. Many complaints and suggestion received from the public transportation users in Bandar Jengka mostly due to the lack of efficiently and effectively public transportation services especially in rural areas. The same problems experienced by the users of public transportation services in the Bandar Jengka where the quality of services provided less than satisfactory that are expected. Therefore the research was carried out to study the effectiveness of public transportation system in the Bandar Jengka towards the student satisfaction.